2005
DOI: 10.1038/sj.npp.1300924
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation is Influenced by Bulbectomy and Normalized by Imipramine Treatment in a Region-Specific Manner

Abstract: Growing evidence indicates that alterations of neuroplasticity may contribute to the pathophysiology of depression. In contrast, various antidepressants increase adult hippocampal neurogenesis and block the effects of stress. These findings result in the 'neurogenesis hypothesis of depression'. The present study seeks to determine out whether cell proliferation is altered in the hippocampus, subventricular zone (SVZ), and basolateral amygdala of adult rats exposed to bilateral olfactory bulbectomy, another est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 58 publications
6
57
0
1
Order By: Relevance
“…Increased neuronal activation in the CeAMY and BLA of the OB rat following open-field exposure confirms that the amygdaloid nuclei are integral in mounting a stress response in these animals. Altered gene expression (Wrynn et al, 2000b) and cell proliferation (Keilhoff et al, 2006) has been previously reported in the BLA of OB rats and this region has been proposed as a potential site of antidepressant activity. The decrease in cFOS expression in the BNST of OB rat would suggest that this area is not activated in response to openfield exposure in the model.…”
Section: Discussionmentioning
confidence: 80%
“…Increased neuronal activation in the CeAMY and BLA of the OB rat following open-field exposure confirms that the amygdaloid nuclei are integral in mounting a stress response in these animals. Altered gene expression (Wrynn et al, 2000b) and cell proliferation (Keilhoff et al, 2006) has been previously reported in the BLA of OB rats and this region has been proposed as a potential site of antidepressant activity. The decrease in cFOS expression in the BNST of OB rat would suggest that this area is not activated in response to openfield exposure in the model.…”
Section: Discussionmentioning
confidence: 80%
“…Adult neurogenesis has been reported in the amygdala of rodents and monkeys (Bernier et al, 2002;Jiang et al, 2014;Takemura, 2005), although the evidence for double labeling of the proliferation marker BrdU and mature neuronal markers is not especially strong. Effects of olfactory bulbectomy, fear conditioning, and fluoxetine have been observed on the numbers of adult-born cells in the amygdala Keilhoff et al, 2006;Okuda et al, 2009), but it is unclear how many of the affected cells are neurons.…”
Section: Neurogenesis In Other Regionsmentioning
confidence: 99%
“…5,16,17 The mechanisms controlling progenitor cell and neuroblast proliferation have not been clarified but circulating factors, including hormones, may play a role. As an example, IGF-I is needed to induce hippocampal proliferation by physical exercise, 18 and stress-elevated circulating levels of adrenal steroids inhibit the production of new granular neurons.…”
Section: Introductionmentioning
confidence: 99%